Anatomical consideration of Temporomandibular Joint, Condylar position among subjects with skeletal malocclusion. - Nabeela Habib, Asma Rafi Chaudhry, Nida Asad Dar, Hafsa Gul, Khurram Shehzad, Muhammad Usman Ghani (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the association between anatomical considerations of TMJ with regard to condylar positioning in Glenoid Fossa and prevalence of malocclusion in patients with TMDs Methods: A thorough investigation was done by collecting data on CT scans of 37 patients with TMDs and their Condylar positioning was recorded. Data on malocclusion was obtained by cephalometric radiographs and the relationship was observed. Results: Our study showed a significant (p<0.05) presence of bilateralism in anterior positioning as well as in posterior positioning. Class II showed significant bilateralism of posterior positioning (n=12, p<0.05) whereas Class III showed significant bilateralism of anterior positioning (n=7, p<0.05) of condyles. Conclusion: Our study on anatomical consideration of TMJ and positions of condyles concluded a significant relevance with orthodontic malocclusion. Posterior positioning of condyles may contribute to Class II whereas anterior positioning of condyles may lead to Class III malocclusion. MeSH Words: Condylar Positions, Malocclusion, TMJ Anatomy.